Denitrification in the deep vadose zone: implications for nitrate leaching under agricultural managed aquifer recharge - Hannah Waterhouse; Helen E. Dahlke; William R. Horwath (Geoderma)
Managed aquifer recharge on agricultural lands (AgMAR) is an inexpensive and extensive form of recharge compared to dedicated recharge basins and injections wells. However, uncertain nitrogen cycling outcomes concerning nitrate (NO3–) transport and fate in the unsaturated zone remain. A combination of laboratory and field experiments were conducted to assess biogeochemical controls on denitrification in surface soils and subsurface sediments during AgMAR. Acetylene block assays were conducted in anaerobic conditions to determine dentification potential rates in the root zone and subsurface sediments collected from an almond orchard down to nine meters in the Central Valley of California. Samples were either amended with carbon (C) and NO3– additions (potential assays) or no substrates were added (control) and nitrous oxide (N2O) was measured over three days. Denitrification potential assays resulted in four times more N2O production near the surface, and 49x more N2O production in the subsurface compared to the control. However, even without additions of C, sediments were able to denitrify ∼ 40 % of the NO3– present in the subsurface during the incubation. Additionally, δ15N of NO3– was measured in the field before and after AgMAR, showing an average absolute increase of 4.0 ‰ in δ15N across 4 m depth suggesting denitrification following AgMAR. Statistical analysis suggests N2O production in assays depends on environmental controls or geochemistry of the soils/sediments when C concentrations are low, with iron significantly influencing denitrification in the control, but not in denitrification potential assays. These results from both laboratory incubations and the field demonstrate initial indications that the vadose zone has the potential to attenuate NO3– via denitrification, however, our results do not allow exact quantification of denitrified N mass under AgMAR, and more work is needed to determine denitrification rates in-situ. Future studies should focus on quantifying denitrification rates in-situ during and immediately following AgMAR events.